A new species of Curius Newman (Coleoptera: Cerambycidae) from Venezuela with notes on sexual dimorphism within the genus - Nearns, Eugenio H.; Ray, Ann M. (Zootaxa, 2006)
A new species, Curius chemsaki (Coleoptera: Cerambycidae: Cerambycinae: Curiini), from Venezuela is described. Features distinguishing the new species from its congeners as well as a key to the four species are presented. Sexual dimorphism in pronotal and prosternal morphology within the genus is also discussed.